Initial performance evaluation of a preclinical PET scanner available as a clip-on assembly in a sequential PET/MRI system. (11th June 2018) - Vrigneaud, J M; McGrath, J; Courteau, A; Pegg, R; Gomis, A Sanchez-Pastor; Camacho, A; Martin, G; Schramm, N; Brunotte, F
Abstract: We evaluated the performance characteristics of a prototype preclinical PET scanner available as an easy clippable assembly that can dock to an MRI system. The single ring version of the PET system consists of eight detectors, each of which comprises a 12  ×  12 silicon photomultipliers (SiPMs) array coupled with a dual layer of offset scintillation crystals to measure depth of interaction. The crystal arrays have 29  ×  29 (30  ×  30 for the outer layer) 4 mm long LYSO crystals (6 mm for the outer layer). The ring diameter is 119.2 mm and the axial field of view is 50.4 mm. The NEMA NU 4-2008 protocol was followed for studying the PET performance. Temperature stability of SiPMs was also investigated. The peak system absolute sensitivity was 4.70% with an energy window of 250–750 keV. The spatial resolution was 1.28/1.88/1.85 mm FWHM (radial/tangential/axial) at a distance of 5 mm from the center. Peak noise equivalent counting rate and scatter fraction for mouse phantom were 61.9 kcps at 14.9 MBq and 21.0%, respectively. The uniformity was 6.3% and the spill-over ratios in the images of the water-and air-filled chambers were 0.07 and 0.17, respectively. Recovery coefficients ranged from 0.13 to 0.96. Change in sensitivity as a function of ambient temperature was 0.3%/°C. These first results indicate excellent spatial resolution performance for use with animal studies. Moreover, the clippable assembly can be upgraded to accept a second ring of SiPMs modules, leading to improved sensitivity and axial coverage.